(untitled) (Pulse, 2018)
Pseudomyxomaperitonei (PMP) is a rare disease characterized by presence of gelatinous ascites and mucinous implants on the peritoneum and omentum. We report the case of a 58 years old woman with primary tumour of the appendix and secondary involvement of other structures & organs of abdominal cavity. Aim of this case report is to create awareness among the clinicians regarding this uncommon disease presented with ascites and irregular masses in the abdomen. In addition, literature on the clinical presentation, diagnostic procedures, and treatment options has been briefly reviewed. Pulse Vol.10 January-December 2017 p.47-51